Cd226−/− natural killer cells fail to establish stable contacts with cancer cells and show impaired control of tumor metastasis in vivo. (3rd August 2017) - Kim, Ji Sung; Shin, Bo Ram; Lee, Hong Kyung; Lee, Jae Hee; Kim, Ki Hun; Choi, Jeong Eun; Ji, A Young; Hong, Jin Tae; Kim, Youngsoo; Han, Sang-Bae
ABSTRACT: CD226 is an activating receptor expressed on natural killer (NK) cells, CD8 + T cells, and other immune cells. Upon binding to its ligands expressed on target cells, CD226 activates intracellular signaling that triggers cytokine production and degranulation in NK cells. However, the role of CD226 in contact dynamics between NK and cancer cells has remained unclear. Our time-lapse images showed that individual wild-type CD226 + NK cells contacted B16F10 melanoma cells for 23.7 min, but Cd226 −/− NK cells only for 12.8 min, although both NK cell subsets showed equal contact frequency over 4 h. On the surface of B16F10 cells, CD226 + cells stayed at the same site with oscillating movement (named stable contact), while Cd226 −/− NK cells moved around at a velocity of 4 μm/min (named unstable contact). Consequently, Cd226 −/− NK cells did not kill B16F10 cells in vitro and did not inhibit their metastasis into the lung in vivo . Taken together, our data demonstrate that CD226 enables prolonged stable interaction between NK and cancer cells, which is needed for efficient killing of cancer cells.